Effect of thrombopoietin-receptor agonists on circulating cytokine and chemokine levels in patients with primary immune thrombocytopenia (ITP). (4th July 2017) - Gudbrandsdottir, Sif; Ghanima, Waleed; Nielsen, Claus H; Feng, Xingmin; Hasselbalch, Hans C; Bussel, James
Abstract: Background: Thrombopoietin-receptor-agonists (TPO-RAs) increase platelet production in Immune Thrombocytopenia (ITP) by stimulating Mpl. The effect of TPO-RAs on inflammatory cytokine production in ITP patients has not been well investigated. Methods : Plasma samples from 48 ITP patients treated with TPO-RAs (median age 50 years (inter-quartile range; IQR 20–69), median platelet counts 24 × 10 9 /L (IQR 15–47 × 10 9 /L), 28 females) and 16 healthy controls (nine females, median age 37 years, IQR 22–51 years) were collected before and during treatment, and analyzed for a panel of cytokines and chemokines by enzyme-linked immunosorbent assay and immuno-bead-based multiplex assay. Results : Elevated levels of C-X-C motif chemokine 10 (CXCL10; p < 0.001) and osteoprotegerin (OPG; p < 0.05) were observed in pretreatment samples compared to controls; these levels decreased during 6 months of treatment. Pretreatment levels of transforming growth factor (TGF)-β were lower than in healthy controls and increased after 6 months of treatment ( p < 0.05). Levels of sCD40L increased after 6 months of treatment ( p < 0.05), but decreased thereafter to pretreatment values. The increase in TGF-β and sCD40L may reflect increased platelet turnover. Levels of tumor necrosis factor (TNF)-α, interferon (IFN)-γ and interleukin (IL)-10 did not change during treatment. Conclusion : These findings suggest that treatment with TPO-RA creates a more balanced steady-state of immune activation.